The risk of influenza infection in the elderly and the role of vaccination in the prevention and reduction of complications - Cvetković, Aleksandra; miljković, ana (PONS - medicinski časopis, 2026)
Introduction The flu poses a serious threat to the elderly due to a weakened immune system and comorbidities. People over the age of 65 face an increased risk of complications, including hospitalizations, cardiovascular problems, pneumonia, and death. According to the World Health Organization (WHO), influenza causes between 250,000 and 500,000 deaths a year, of which 38,500 are estimated in Europe. Aim of the paper To investigate the risks posed by influenza to the elderly population, with a focus on comorbidities and the impact of vaccination in reducing these risks, as well as the benefits of new vaccines for this risk group. Discussion The risk of complications increases with age and concomitant diseases. Cardiovascular complications, including heart attacks and worsening heart failure, are often the result of influenza infection. Pneumonia is the leading cause of mortality, occurring in 10% of those infected. Although the immune response to vaccines may be weaker in the elderly, research shows that vaccination significantly reduces the risk of severe outcomes. A new generation of vaccines, such as high-dose and adjuvant vaccines, improve the immune response and protection. Conclusion Influenza vaccination provides significant protection for the elderly, reducing the severity of the disease and the mortality rate. Advances in the development of new vaccines improve outcomes in this risk group, making vaccination a key strategy in preventing complications of influenza. Keywords: influenza virus, influenza, vaccination, aging, complications, vaccine effectiveness